Molecular survey of zoonotic Anaplasma phagocytophilum and genetic evidence of a putative novel Anaplasma species in goats from Taif, Saudi Arabia - Mohamed W. Ghafar (International Journal of One Health, 2019)
Aim: Genus Anaplasma is of veterinary and public health importance, and its members utilize ruminants as key hosts in their epidemiology. To date, information about the occurrence and molecular identity of Anaplasma phagocytophilum and other Anaplasma species in Saudi Arabian goats is scarce. This study aimed to molecularly detect and characterize zoonotic A. phagocytophilum and other Anaplasma spp. in goats from Taif District, KSA.